Análise estrutural de filmes finos de hematita produzidos por spin-coating para geração de hidrogênio - Lima, Bruno Henrique Ramos de (2010)
Water photolysis at semiconductors is a clean and renewable method for solar energy conversion into hydrogen fuel. Hematite (-Fe2O3) thin films have been presented as a promissory material for water photolysis due to it s abundance, chemical stability, environmental compatibility and appropriate band gap energy to absorb a large part of the solar spectrum and for the water photooxidation process. In this work the influence of synthesis and deposition parameters on the microstructure and photoelectrochemical properties were studied. The films were produced on FTO substrates by spin-coating deposition of Fe+3 polymeric resin prepared by complex polymerization method using ethanol as a solvent. Doped films were prepared by addition of tetraethylortosilicate (TEOS) in Fe+3 resin. Characterizations were made by xrays diffraction, UV-Visible spectroscopy and scanning electronic microscopy. Photoelectrochemical properties were measured in a three-electrode standard electrochemical cell, with the film as a work electrode, platinum as a counter electrode and Ag/AgCl in KCl satured solution as reference electrode. Results have shown that substrate-film interface is responsible for the formation of three regions with distinct morphologies and have shown that just a small percentage of the films are in direct contact with the substrate and contributes with photocurrent. The better silicon incorporation in hematite structure using ethanol as a solvent was also observed. The best photocurrent density were obtained by one layer silicon doped films, at 0,6 V in 1M NaOH electrolyte.